Feminism and behavior analysis: pathways to dialogue - Couto, Aline Guimarães; Dittrich, Alexandre (Perspectivas em Análise do Comportamento, 2017)
Feminism, as a political theory and social movement, has been maintaining productive dialogues with science, influencing critical revisions and new ways of analyzing human behavior, even in psychology. Such influence is not consistently observed in behavior analysis’ scientific publications, which relies only on sparse publications about overcoming gender inequalitiess. is paper brie y reviews articles about feminism in behavior analytic journals, also making some notes about the theoretical-practical approaches pointed out by these produc- tions, intending to contribute to progresses for behavior analysis in women’s studies.